The Functioning of the English Language in the Educational, Political and Cultural Spheres of Belgium - G. A. Demin (Дискурс, 2024)
Introduction. The English language continues to spread around the world, exhibiting a globalist function. The relevance of the presented research lies in the interest that follows from this fact in the positions of this language in countries where it is not a native or a state one. Belgium, as one of the important European centers from a socio-political point of view, is also a unique case due to the linguistic situation present in the country related to the Dutch and French languages. The purpose of this work is to analyze the position of the English language in Belgium in various areas and try to determine the trends in its development in the European state.Methodology and sources. The research materials include statistical data obtained as part of a study of the level of English language proficiency, recordings of speeches of the Prime Minister of Belgium at the UN, as well as information from the website of the Cannes Film Festival. Additionaly, results of the researchers Janssens and Hertogen concerning the language situation in Belgium are addressed. This work uses methods of synthesis and analysis, observational and descriptive methods, as well as a comparative method.Results and discussion. Belgium is one of the most advanced countries in terms of English language proficiency. Despite the existing ambiguous linguistic situation between the official languages of Belgium, English is not only able to make its way into this environment, but also has a fairly high influence. This is noticeable in the field of higher education, where, albeit with varying percentages by region, each of Belgium's most prestigious higher education institutions has programs in English. We can talk about a similar influence in the political sphere, since some major political figures in Belgium predominantly prefer English, even on those platforms where French is one of the languages of these platforms. However, the example of cinema shows that English is still poorly spread in the cultural sphere of life in Belgium.Conclusion. Younger generations of Belgium are accelerating their learning and mastery of English, playing a role in establishing very high levels of English proficiency. The contradictions that are reflected in the sphere of culture, partly in the sphere of higher education, as well as in the falling rates of language proficiency among older generations, ultimately do not alter those factors that allow us to say about the widespread and possible increase in the role of this language in the social language environment of Belgium.